Development and Management of SME Industries in the City of Tanjungpinang - Nurhasanah, Nurhasanah; Tiyasiningsih, Ezky (Priviet Social Sciences Journal, 2023)
Small and Medium Enterprises (SMEs) serve as vehicles that unite, direct, and cultivate the creative, innovative, and entrepreneurial capabilities of the community, especially in Tanjungpinang City. However, the operation of SMEs is not without various challenges, including low productivity due to the quality of human resources, limited production tools, insufficient capital, and inadequate financial management. Small-business activities often face failure or bankruptcy due to the lack of ability to manage finances effectively. SMEs located in industrial areas need knowledge input to develop their businesses. In this regard, the role of the government is crucial in fostering and providing training for SMEs, especially in Tanjungpinang. Training activities in management and financial aspects are expected to assist businesses like "Yan Tenun" in improving the quality and quantity of production and financial management. The service program encompasses understanding business management to financial administration for business owners.